The Countryside Scenery Reflected in We Both Live in The Same Village by Rabindranath Tagore - Christine Resnitriwati Respatio (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
AbstractFor the people who live in a big, crowded city, visiting a countryside or village is something that would make them feel happy. In countryside, it has always beautiful and natural scenery, peaceful atmosphere, cool and clean air and humble, simple lives of villagers.  People can walk and ride a horse to go around the objects in a village, for examples flowers and fruits gardens or barley and rice fields.  People can swim and bathe in the river, do the activities in the village market with their neighbors and enjoy the harvest season for mango or linseed.  The beauty in a village was expressed by Rabindranath Tagore in his poem We Both Live In the Same Village and the writer will analyze that poem through intrinsic elements (imagery, personification and repetition) to understand deeper about the sense of the poem, and extrinsic elements to understand the situation and the characteristic of a country side.Keywords: countryside, flowers, fruits, river, fields